Comparison of Fos expression within the ferret's spinal trigeminal nuclear complex evoked by electrical or noxious-thermal pulpal stimulation - Siriporn Chattipakorn (2018)
Fos-like immunoreactivity (Fos-LI) was used as a marker of trigeminal neurons that responded to tooth pulp stimulation. The activation of intradental afferents was produced by electrical stimulation of the ferret's intact canine tooth, whereas natural stimuli that activate predominantly Aδ (5 mol/L CaCl2applied to dentin) or C fibers (slow heating of the intact tooth) were used to stimulate the 2 populations of afferents selectively. Electrical stimulation evoked Fos-LI in ipsilateral dorsomedial of the trigeminal subnucleus caudalis (Vc), dorsomedial and ventrolateral of the transition zone between subnucleus interpolaris and caudalis (Vi/Vc), and the the paratrigeminal nucleus (Pa5). Osmotic stimulation evoked Fos-LI in the ipsilateral dorsomedial Vc and Vi/Vc. The spatial distribution of Fos labeling after heat stimulation was dependent on the duration and location of the stimulus application. Repeated heating of the maxillary canine for 30 minutes evoked labeling bilaterally in ventrolateral Vi/Vc. Stimulation of the maxillary and mandibular canines with heat pulses for 1 hour produced labeling in the ipsilateral dorsomedial Vc, dorsomedial Vi/Vc, and the Pa5. None of the stimulating procedures did evoke Fos expression in regions rostral to Vi/Vc. Regardless of the pulpal stimulation procedures, a similar number of Fos-positive neurons was found in the nucleus of solitary tract and the ventrolateral medulla. Although Fos expression does not reveal all neurons that respond to noxious pulpal stimulation, it marks many neuronal regions that contain neurons that respond to pulpal stimulation and injury. Our results suggest that a population of neurons in Vc and Vi/Vc contribute to painful sensations originating from the dentition. © 2005 by the American Pain Society.